Penerapan Sistem Otomatis Konversi Minyak Jelantah menjadi Lilin Aromaterapi - Hasvienda M Ridlwan; Ahmad Adifani; Vernida Mufida (MBI, 2023)
This research focuses on the development of an automated system for the production of aromatherapy candles using waste cooking oil. The study addresses the challenges faced in small-scale production, including limited capacity, manual processes, and inconsistent product quality. To overcome these challenges, an automated machine is proposed to improve efficiency and productivity. The homogenization process and heating time were identified as critical areas for improvement. A sequential control system was successfully implemented, enabling the conversion of waste cooking oil into aromatherapy candles with a production capacity of 10.5 liters per unit run. The motor control system utilized On-Off control with modified power input to minimize vibration issues, operating the motor at 50-60 RPM. The temperature heater control system employed a PID control method, specifically the Ziegler-Nichols type 2 method, with Kp and Ki values of 247.5 and 1.104, respectively. The chosen PID parameters demonstrated satisfactory performance, including a rise time of 22.95 minutes, maximum overshoot of 2.85%, and a dead time of 510 seconds. The implemented system was controlled using an Arduino controller, ensuring a fast response and stable operation.